2023
DOI: 10.1038/s41467-023-36887-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving adenine and dual base editors through introduction of TadA-8e and Rad51DBD

Abstract: Base editors, including dual base editors, are innovative techniques for efficient base conversions in genomic DNA. However, the low efficiency of A-to-G base conversion at positions proximal to the protospacer adjacent motif (PAM) and the A/C simultaneous conversion of the dual base editor hinder their broad applications. In this study, through fusion of ABE8e with Rad51 DNA-binding domain, we generate a hyperactive ABE (hyABE) which offers improved A-to-G editing efficiency at the region (A10-A15) proximal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Finally, the rate of on-target indels was estimated to be ≤1.2% for all target loci (0.6, 1.2 and 0.2% for FLT3 , CD123 and KIT , respectively) (Extended Data Fig. 8d ), consistent with previously reported data for ABE 42 , 43 . Overall, these data support a generally safe genotoxicity profile of FLT3, CD123 and KIT epitope editing in CD34 + HSPCs.…”
Section: Off-target Effects Of Epitope Editingsupporting
confidence: 90%
“…Finally, the rate of on-target indels was estimated to be ≤1.2% for all target loci (0.6, 1.2 and 0.2% for FLT3 , CD123 and KIT , respectively) (Extended Data Fig. 8d ), consistent with previously reported data for ABE 42 , 43 . Overall, these data support a generally safe genotoxicity profile of FLT3, CD123 and KIT epitope editing in CD34 + HSPCs.…”
Section: Off-target Effects Of Epitope Editingsupporting
confidence: 90%
“…It has been reported that fusing a single-strand DNA-binding domain from RADIATION SENSITIVE 51 (Rad51) to a cytosine base editor [ 26 ] or adenine base editor [ 27 , 28 ] could enhance the base editing capability in mammalian cells and rice. We wondered if the fusion of Rad51 could influence the editing efficiency of TALE-DdCBEs; therefore, we inserted the Rad51 domain before the DddA halves or before the TALE N-terminal domain (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the second-generation DuBEs, ABE7.10 was replaced with high-performing monomeric ABE variants to increase the likelihood of greater simultaneous A-to-G and C-to-T edits. Notably, TadA-8e (ABE8e) adoption in DuBEs showed higher concurrent BE activities in distinctive DuBE architectures developed by various research teams, such as iACBEs ( 42 ), ACBE ( 43 ), CABE-RY ( 44 ), ACEs ( 5 ), Dual BEs ( 45 ), and hyA&C-BEmax ( 46 ) ( Table 1 ). Recently, ACBE variants without the UGI domain or with the UGI domain replaced by uracil-DNA glycosylase (UNG) have shown increased randomization of deaminated Cs into all possible outcomes (C-to-G/T/A) along with A-to-G and indels, termed as AGBEs ( 47 ).…”
Section: Be-trm Toolbox For Directed Evolutionmentioning
confidence: 99%